Determination of coal rock strength properties according to geophysical well survey ( the South-Yakut coal basin) (Proceedings of Voronezh State University. Series: Geology, 2019)
The article represents the research results in the field of data application of the geophysical well survey for determination of strength properties of coal massif by the example of the South-Yakut coal basin. The authors defined estimability of representativeness of the initial data of the geophysical well survey in accordance with the caliper logs with the aim of exception of wrong determination of the strength properties of the coal massif and their further inclusion in the database, used in computer modelling of coal deposits. The article considers the approximating function, established in the authors’ research, which allows more efficient determination of strength properties of the coal massif in compliance to the geophysical well survey for the conditions of the South-Yakut coal basin. In addition, the authors represent calculating equations for determination of strength characteristics at uniaxial compression and extension of coal massif in the South-Yakut coal basin according to the data of caliper logs and gamma-ray logging. The authors determined weigh coefficients of the geophysical parameters for some coal bearing regions of the South-Yakut coal basin, increasing determination accuracy of ultimate strength at uniaxial compression and extension of the coal-bearing rocks. The article contains examples of estimation of the representativeness of the initial geophysical data according to the caliper logs and determination of the ultimate strength at uniaxial compression and extension of coal-bearing rocks of the Elginsk coal deposit, as a part of the South-Yakut coal basin.
Keywords: geophysical well survey; strength properties of coal massif; estimability of representativeness of the initial data of the geophysical well survey; determination method of strength properties of coal-bearing rocks; the South-Yakut coal basin